US Police Department’s Representation in The New York Times Article “George Floyd’s Brother Pleads with Congress: ‘Make it Stop’”: A Critical Discourse Analysis - Sherine Gracia Yudhi; Trisnowati Tanto (Universitas Sanata Dharma, 2022)
The study aims to examine the representation of the US Police Department in a foreign media news article, The New York Times, entitled “George Floyd’s Brother Pleads with Congress: ‘Make it Stop’”. The text itself discusses an incident of brutality and systemic racism involving the US Minneapolis police officers towards George Floyd, an African-American, which leads to his death. This incident can be considered to be one of the biggest news that attracts the most attention, reaction, and action all over the world in 2020. This research uses Critical Discourse Analysis proposed by Teun A. van Dijk, focusing only on the micro-level analysis: macrostructure, microstructure, superstructure. There are four linguistics tools applied in the microstructure, which are rhetorical question, lexicalization, metaphor, and implication. The qualitative descriptive method is the research method used. Since the data are collected by searching for information in the Internet and other printed references, this research is also categorized into a library research for the fact that it has a wide scope of sources, including the academic journal, newspapers, magazine, e-books, relevant web resources, and various multimedia. The result shows that through these three aspects of the microstructure analysis, the author portrays a negative representation of the US Police Department.